Implementation of the Simple Multi Attribute Rating Technique (SMART) Method on the Decision Support System for Determining Revolving Fund Capital Loan Receipt at the Cooperative Service - Annisa Dwi Putri; liza yulianti; devi sartika (Jurnal Komputer, Informasi dan Teknologi, 2021)
The purpose of writing this final project is to find or recommend recipients of revolving fund borrowings at the cooperative office, therefore a Decision Support System is needed for the recommendation for acceptance of revolving capital loans at the cooperative office using the smart method. The research method applied in this research is the development of the waterfall method. The waterfall method is a systematic and sequential information system development model Implementation of the Smar Method in a Decision Support System for determining the acceptance of a revolving fund capital loan at the cooperative service is an algorithm for processing data based on the weight of the criteria. The Samrt method is a method used to determine the acceptance of a revolving fund capital loan based on the weight of the criteria, at the Cooperative Service there are six criteria, namely, capital range, rate, number of members, cooperative status, legal entity, length of establishment, each decision is calculated based on the six criteria above. Decision Support System Recommendation Revolving fund loan acceptance is built using Visual Basic programming language and Microsoft Access database. The Decision Support System produced in this study can display cooperative data and the ranking of the results of receiving revolving fund loans based on existing data so that it can be used as a solution or consideration in the process of receiving revolving fund loans.